Flood modeling using GIS-based watershed hydrological model and remotely sensed data / Abolghasem Akbari - Abolghasem, Akbari (2011)
Due to land use and climate changes, more severe and frequent floods occur worldwide. Flood simulation as the first step in flood risk management can be robustly conducted with an integration of GIS, RS and flood modeling tools. The primary goal of this thesis is to examine the practical use of public domain satellite data and GIS-based hydrologic model. To achieve all objectives of this research, firstly the value and importance of data in water resources engineering specifically for rainfall runoff modeling is discussed. A review of the literatures is provided on modeling concept, watershed models and its classification; spatial data model and its application in hydrology are presented. In addition, common approaches that GIS integrates with hydrologic models are reviewed and basic concept of surface-runoff modeling and its equations that relates to this subject are presented. Secondly, database development using raw data collected from different sources is described. GIS tools and techniques were used in the light of relevant literature to achieve the appropriate database. Watershed delineation and parameterizations were carried out using cartographic DEM derived from digital topography at a scale of 1:25000 with 30 m cell size and SRTM elevation data at 90 m cell size that originally were acquired in 30 m resolution. The SRTM elevation dataset is evaluated and compared with cartographic DEM. Advanced and novel GIS techniques were used for DEM manipulation and watershed delineation. The research questions were answered with the assistance of statistical measures such as Correlation coefficient (r), Nash-Sutcliffe efficiency (NSE), Percent Bias (PBias) or Percent of Error (PE). The results are described in detail with the assistance of several tables and illustrations. Based on NSE index, SRTM-DEM can be used for watershed delineation and parameterization with 87% similarity with Topo-DEM in a complex and underdeveloped terrains. Overall agreement is significantly achieved (95%) when only non-urbanized areas with rugged topography are considered. However NSE (33%) exhibits a high level of discrepancy between Topo and SRTM DEM-derivatives in urbanized areas with mild slope. Spatio-temporal variations of rainfall events over Klang watershed are discussed to achieve the one of other objectives of this study. Primary investigation is made for eight floods resultant from rainfall events in 2002. Then four rainfall events were selected for further analysis. Kriging interpolation is used to define the areal distribution of rainfall over the study area. The same rainfall events acquired by TRMM (V6) were analyzed and compared with the gauge data. It is concluded that TRMM estimates do not give adequate information about the storms as it can be drawn from the rain gauges. A pure and novel GIS analysis and flood simulation model supported by two public domain satellite data was conducted. Event-based comparison is made for TRMM precipitation estimates with the rainfall catch at rain gauges. Then evaluation is followed by rainfall-runoff modeling using HEC-HMS. Several conclusions at the technological and application levels have been achieved with this research. At the technological level, GIS has proven to be a useful tool with the ability to extract multiple parameters from a DEM and create a hydrological database from it. At the application level, it was proved that SRTM elevation dataset has the ability to obviate the lack of terrain data for hydrologic modeling where appropriate data for terrain modeling and simulation of hydrological processes is unavailable. However TRMM precipitation estimates failed to explain the behavior of rainfall events and its resultant peak discharge and time of peak. However TRMM data could reasonably simulate the volume of outflow for investigated flood event.